2018
DOI: 10.1093/tas/txy148
|View full text |Cite
|
Sign up to set email alerts
|

The impact of “super-dosing” phytase in pig diets on growth performance during the nursery and grow-out periods1

Abstract: Previous research indicates that “super-dosing” phytase may improve pig growth performance by improved nutrient use, although the benefits appear to be more consistent in nursery than in grow-out pigs. Therefore, two experiments were conducted to determine if performance could be improved by feeding phytase at super-dosed levels, and whether this response would be different if energy and amino acid (AA) were limiting. Experiment 1 involved 440 weaned pigs (6.27 ± 0.01 kg) in a factorial arrangement of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…The very low protein diet decreased the feed efficiency and growth performance of pigs, which was similar to previous studies [ 9 , 10 , 11 ]. The beneficial effects of microbial phytase as a feed additive on the growth performance of pigs fed with amino acids-deficient diets have been documented previously [ 28 , 29 ], but it is unknown whether the negative effects of low protein diets can be mitigated by using phytase produced in transgenic plants. Although both doses of CEP (i.e., 2000 and 4000 FTU/kg) showed some promising effects on certain parameters, it seems that 4000 FTU/kg CEP had added benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very low protein diet decreased the feed efficiency and growth performance of pigs, which was similar to previous studies [ 9 , 10 , 11 ]. The beneficial effects of microbial phytase as a feed additive on the growth performance of pigs fed with amino acids-deficient diets have been documented previously [ 28 , 29 ], but it is unknown whether the negative effects of low protein diets can be mitigated by using phytase produced in transgenic plants. Although both doses of CEP (i.e., 2000 and 4000 FTU/kg) showed some promising effects on certain parameters, it seems that 4000 FTU/kg CEP had added benefits.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting reports on the effects of microbial phytase on the digestibility of N and amino acids in pigs [ 26 , 27 ]. Some studies have shown promising outcomes on growth performance when microbial phytase was used for pigs receiving amino acids-deficient diets [ 28 , 29 ], but some others have reported no positive effects on the growth of animals [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, phytase allows adjustments around the inclusion of inorganic macromineral sources in diet formulations. High levels of added phytase (superdosing) have been observed to enhance nutrient digestibility and pig growth performance and have been observed to be more effective during the nursery phase than the grow-finish phase ( Holloway et al, 2019 ). Proteases, another commonly used enzyme in monogastric diets, may increase the rate of hydrolysis of protein sources, increasing AA availability and reducing N excretion.…”
Section: Introductionmentioning
confidence: 99%
“…In the finishing phase, the pigs supplemented with 1500 and 3000 FYT (i.e., the NC15 and NC30 treatments) had higher live weights at 112 days old ( p < 0.05), as did the pigs in the PC treatment (without reductions in Ca and P). Studies conducted by Holloway et al [ 9 ] showed that phytase levels between 1000 and 2500 FYT/kg of feed improved the performance (DWG and FCR) of finishing pigs, resulting in a higher slaughter weight. The better performance in this period can be credited to the fact that progressively higher amounts of phytase in the diet increased the plasma levels of blood inositol of the animals in the finishing phase [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially related to energy, this enzyme shows a similar result compared with the exogenous carbohydrases, which improve the availability of food energy and together can potentiate this effect [ 6 ]. Commercially, there are several sources of exogenous phytase available for use in monogastric nutrition, the synthesis of which is derived from isolated yeast or bacteria [ 7 , 8 , 9 ], such as Buttiauxella spp. [ 10 , 11 , 12 ], Aspergillus niger [ 13 , 14 ], Citrobacter braakii [ 8 , 15 , 16 ] and Escherichia coli [ 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%